2021
DOI: 10.3389/fnbeh.2021.722780
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Domain Touchscreen-Based Cognitive Assessment of C57BL/6J Female Mice Shows Whole-Body Exposure to 56Fe Particle Space Radiation in Maturity Improves Discrimination Learning Yet Impairs Stimulus-Response Rule-Based Habit Learning

Abstract: Astronauts during interplanetary missions will be exposed to galactic cosmic radiation, including charged particles like 56Fe. Most preclinical studies with mature, “astronaut-aged” rodents suggest space radiation diminishes performance in classical hippocampal- and prefrontal cortex-dependent tasks. However, a rodent cognitive touchscreen battery unexpectedly revealed 56Fe radiation improves the performance of C57BL/6J male mice in a hippocampal-dependent task (discrimination learning) without changing perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 129 publications
2
38
0
Order By: Relevance
“…However, in a different study, we found that 0.10 Gy 56 Fe irradiation did not impair fear memory in male APP/PS1 mice 6 months after irradiation, though both males and females showed impairment on the novel object recognition test [20]. Of note, one recent study found that fractionated 56 Fe improved hippocampal-dependent memory but impaired striatal-dependent memory in female WT mice [41]. 56 Fe is one of many heavy ions that astronauts will encounter in space, and sex differences have been reported with other ion species as well.…”
Section: Discussionmentioning
confidence: 62%
“…However, in a different study, we found that 0.10 Gy 56 Fe irradiation did not impair fear memory in male APP/PS1 mice 6 months after irradiation, though both males and females showed impairment on the novel object recognition test [20]. Of note, one recent study found that fractionated 56 Fe improved hippocampal-dependent memory but impaired striatal-dependent memory in female WT mice [41]. 56 Fe is one of many heavy ions that astronauts will encounter in space, and sex differences have been reported with other ion species as well.…”
Section: Discussionmentioning
confidence: 62%
“…1A ) underwent touchscreen behavioral testing 1 week post-surgery. Touchscreen experiments were performed between 08:00 to 14:00 during weekdays (Soler et al, 2021). As is standard in most rodent touchscreen experiments, mice were food restricted during touchscreen experiments.…”
Section: Methodsmentioning
confidence: 99%
“…General Touchscreen Training (prior to LDR) or "General TS Train" (Fig. 1A), consists of five stages (Whoolery et al, 2020;Soler et al, 2021): Habituation, Initial Touch, Must Touch, Must Initiate, and Punish Incorrect (PI). Methods for each stage are described in turn below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Creative problem solving utilizes several executive functions involved in planning, organization, decision making, judgment, task monitoring, attention, hypothesis generation, abstract thinking, and cognitive flexibility (Stuss and Levine, 2002;Cato et al, 2004;Sue Baron, 2004;Spinella, 2005). Regrettably, ground-based rodent experiments suggest that exposure to ≤25 cGy of several SR ions (i.e., protons, 4 He, 16 O, 28 Si, 48 Ti and 56 Fe) impairs various aspects of executive function but primarily cognitive flexibility tasks (Britten et al, 2014;Davis et al, 2014;Parihar et al, 2015;Britten et al, 2018;Jewell et al, 2018;Parihar et al, 2018;Acharya et al, 2019;Britten et al, 2020a;Britten et al, 2020b;Whoolery et al, 2020;Britten et al, 2021a;Burket et al, 2021;Soler et al, 2021;Britten et al, 2022).…”
Section: Introductionmentioning
confidence: 99%